Moonshot: Affordable, Simple, Flight Hardware for the Artemis-1 Mission and Beyond - Hammond, Timothy G.; Allen, Patricia L.; Wells, Howard W.; Russick, James M.; Nislow, Corey; Giaever, Guri; Birdsall, Holly H. (Frontiers in Space Technologies, 2020)
Artemis is a NASA initiative to return US astronauts to the moon and beyond. Artemis includes a robust science program. A key to space-based biological science is the ability to construct high quality, efficacious scientific hardware cheaply and in a short time frame. We report the design and fabrication of affordable new flight hardware to support the growth of Chlamydomonas reinhardtii, a single-cell green alga on the Artemis-1 mission. Chlamydomonas reinhardtii, produces two products of great interest to space travel - lipids as a source of bioproducts and hydrogen a source of fuel. We will use this hardware to grow a library of mutant strains to identify Chlamydomonas reinhardtii genes that optimize survival and fuel production during exposure to the combined impacts of space radiation and microgravity in the cosmic space environment beyond the van Allen belts. Using fitness as a readout a library of mapped insertion mutant strains will be grown competitively during exposure to space radiation and microgravity. This report describes the hardware and the science verification test that validates its utility for missions ahead. This hardware can be easily adapted to a broad range of uses and microbes and its low cost will make space science affordable and practical.